(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2020)
The cultivation of medicinal plants ensured a stable supply of qualitative raw materials in the drug industry. At the same time, it encourages reservation of important and unique resources of medicinal plants. Pharmacognostic characteristics of roots from Astragalus membranaceus (Fisch.) Bge and Astragalus mongolicus Bge cultivated in the Kherlen Bayan-Ulaan, Khentii aimag in Mongolia have been analyzed. Namely, qualitative characteristics of roots were analyzed according to the methods of Mongolian National Pharmacopoeia and the quantity of active compound saponins was analyzed by the spectrophotometric method, including their permissible limits. According to the experiments, moisture in the two roots was determined as 10.0%. Total ash from the roots was 2.38±0.05% in A.membranaceus and 4.18±0.86% in A.mongolicus respectively. Acid-insoluble ash was 0.16±0.04% and 0.28±0.07%, water-extracted compounds were 26.83±0.30% and 37.51±1.62%, respectively, which were assured the standard requirements. The quantity of active compound saponins in the root of A.membranaceus was determined at 0.044±0.009%, while in A.mongolicus 0.028±0.006%. Hence, the root of A.mongolicus contains more water soluble compounds, especially polysaccharides, while A.membranaceus contains more saponin glycosides. Тарималжуулсан хоёр зүйл Хунчирын эмийн түүхий эдийн стандартчиллын асуудлууд Хураангуй: Эмийн ургамлыг тарималжуулан хэрэглэх нь үйлдвэрлэлийг стандартын шаардлага хангасан түүхий эдээр тасралтгүй ханган нийлүүлж явуулах нэг арга болохын зэрэгцээ тухайн зүйл ургамлыг хамгаалах ач холбогдолтой. Манай орны Хэнтий аймгийн Хэрлэнбаян-Улаанд тарималжуулсан Сарьслаг хунчир, Монгол хунчирын үндэс түүхий эдийн чанарын тоон үзүүлэлтүүдийг Монгол Улсын Үндэсний Фармакопейнд бичигдсэн арга зүйн дагуу, биологийн идэвхт үйлчлэгч гол нэгдэл сапонины тоо хэмжээг спектрофотометрийн аргаар тодорхойлж, тэдгээрийн зөвшөөрөгдөх хязгаарыг тогтоов. Туршилт судалгааны дүнд хоёр зүйл хунчирын үндэсний чийг 10.0%, нийт үнс Сарьслаг хунчирынх 2.38±0.05%, Монгол хунчирынх 4.18±0.86%, сулруулсан HCI-д үл уусах үнс 0.16±0.04% ба 0.28±0.07% гэж зөвшөөрөгдөх хязгаарт, нэрсэн усанд хандлагдах бодисын хэмжээ 26.83±0.30% ба 37.51±1.62% байгааг тодорхойлов. Биологийн идэвхт үйлчлэгч нэгдэл сапонин нь Сарьслаг хунчирын үндсэнд 0.044±0.009%, Монгол хунчирынхад 0.028±0.006% тус тус агуулагдаж байна. Эндээс Монгол хунчирын үндсэнд усанд уусдаг бодисууд, ялангуяа полисахар их хэмжээтэй, харин Сарьслаг хунчирын үндсэнд сапонин гликозид илүү агуулагдаж байгааг тогтоов. Түлхүүр үг: Сарьслаг хунчир, Монгол хунчир, фармакогнозын чанарын үзүүлэлт, нийт сапонин